(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Wire chairs, starting from the designs of Charles and Ray Eames (DKR Wire Shell, 1951) and Harry Bertoia (Diamond Chair 1952, Side Chair 1952), are a particular field of investigation for both the design historian and the designer. The geometry of their “shell” and supporting structure is still able to puzzle and charm. They are “sculptures made of air”, as Bertoia used to say, yet they are made of a simple industrial material. As true works of art, they fit in any kind of interior. They are often sought as precious vintage collectors’ items. The authors seek to identify the general and particular features of these mid-century modern classics that had an iconic role in setting new forms and concepts, and to follow a part of their influence upon 21st century design. The analysis itself is allowed to develop into a design process, set between the spatial geometry of an artwork and the functional requirements of the chair.